2020
DOI: 10.1039/d0sc00244e
|View full text |Cite
|
Sign up to set email alerts
|

Dearomatization of aryl sulfoxides: a switch between mono- and dual-difluoroalkylation

Abstract: Herein we describe the dearomatization of aryl sulfoxides with difluoroenol silyl ether (DFESE) using a rearrangement/addition protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 60 publications
(4 reference statements)
0
12
0
1
Order By: Relevance
“…[13] Further studies revealed that the choice of bases was also critical to the reaction. Pyridine derivatives were more effective than aliphatic tertiary amines (entries [10][11][12][13]. Further optimization of the reaction temperatures and reaction times identified the best conditions giving 5aa in 71 %yield (entry 16).…”
Section: Resultsmentioning
confidence: 99%
“…[13] Further studies revealed that the choice of bases was also critical to the reaction. Pyridine derivatives were more effective than aliphatic tertiary amines (entries [10][11][12][13]. Further optimization of the reaction temperatures and reaction times identified the best conditions giving 5aa in 71 %yield (entry 16).…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, Peng and co-workers reported a dearomatization strategy involving aryl sulfoxides 49a and the difluoroenol silyl ether (DFESE) 49b, as a highly effective nucleophilic rearrangement partner, to generate dearomatized products 49c and 49d (Scheme 49). 86 This protocol represents the first example of a dearomatization reaction in aryl sulfoxide chemistry. Depending on the electrophilic activator employed (TFAA or Tf 2 O), this transformation delivers dearomatized products 49c and 49d possessing either mono-or bis-difluoroalkyl groups.…”
Section: Review Synthesismentioning
confidence: 99%
“…1a , product IV and VI ) 39 . Recently, several excellent studies aiming to address the activity issues were achieved by developing new catalytic model 8 , 32 or using energetic intermediates and substrates 37 , 38 , 40 , 41 . For example, Peng group disclosed a dearomative dual functionalization of aryl iodanes by integration a iodonio-Claisen rearrangement with a subsequent nucleophilic interception of the dearomative intermediate (Fig.…”
Section: Introductionmentioning
confidence: 99%